The Torment of Preaching and Listening in a Pluralistic Society - Marian Šuráb (Polonia Sacra)
The homily is an act of communication that consists of three elements: the preacher, the listener, and the homily. The purpose of homilies is to update the message of salvation and encourage the faithful to live the gospel. The homily as communication should take place in a peaceful environment. If this is not the case, preaching and listening may result in suffering. The paper mentions several reasons why this happens. The preacher may suffer from a new cultural and religious circumstance, authority issues, impaired spirituality, personal difficulties, loss of enthusiasm and fear or excessive stage fright. For listeners, the torment of listening may be caused by unfulfilled expectations, a bad relationship with the preacher, or homilies that lack simplicity, are full of abstract sentences, are long or unprepared.